2021
DOI: 10.1101/2021.05.03.21256553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Dexmedetomidine in Children using Real World Data from Electronic Health Records and Remnant Specimens

Abstract: Dexmedetomidine is commonly used as part of intraoperative anesthetic management and for sedation and pain control after surgery in children. Dexmedetomidine infusion dose is typically given on a fixed weight basis with titration to achieve sedation goals while avoiding potential toxicities. Pharmacokinetic (PK) studies are useful for accurate prediction of the individual dose required to achieve sedation and analgesia goals without toxicity, but lack of PK data is a challenge in precision dosing for pediatric… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“… Observed concentrations vs. population predicted concentrations using previously published pharmacokinetics models in children. Observed concentrations vs. population predicted concentrations using population pharmacokinetics models developed by (1) Potts et al ( 12 ), (2) van Dijkman et al ( 13 ), (3) Greenberg et al ( 14 ), (4) Su et al ( 15 ), (5) Damian et al ( 16 ), and (6) James et al ( 17 ). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Observed concentrations vs. population predicted concentrations using previously published pharmacokinetics models in children. Observed concentrations vs. population predicted concentrations using population pharmacokinetics models developed by (1) Potts et al ( 12 ), (2) van Dijkman et al ( 13 ), (3) Greenberg et al ( 14 ), (4) Su et al ( 15 ), (5) Damian et al ( 16 ), and (6) James et al ( 17 ). …”
Section: Resultsmentioning
confidence: 99%
“…We therefore decided to determine whether models that were published in the literature in children who were not treated with ECMO were able to predict the data that we derived from our study. To this end, we identified six population PK models of intravenous dexmedetomidine (Table 1) (12)(13)(14)(15)(16)(17) and used external validation methods to compare our observed concentrations in children on ECMO with predicted concentrations using each model and the dosing information for each subject. The models were selected because they were developed in a population including infants <1 year old, which represent most of our population, and were described in sufficient detail in the original manuscript to be reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen UGT proteins have been identified in humans, and they are divided into two families, UGT1 and UGT2, and UGT2 is subdivided into two subfamilies UGT2A and UGT2B ( Nakamura et al, 2008 ). James et al indicated that the UGT1A4 or UGT2B10 genotype does not affect the pharmacokinetics of dexmedetomidine in children ( James et al, 2021 ). Similarly, SNPs in the UGT candidate genes screened in our study were not associated with pharmacokinetic parameters or drug effects of dexmedetomidine in adult female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Higher dose needs in younger patients (<1 year) have been reported 15 and pediatric pharmacokinetic models of dexmedetomidine have demonstrated age-related changes. 9,[56][57][58] Though the understanding of the effect of age on relevant pharmacokinetic and pharmacodynamic pathways remains incomplete, maturation of metabolic pathways, receptor expression, and receptor functionality have been postulated to contribute. 56 In contrast to age, few pharmacokinetic studies have evaluated albumin as a covariate.…”
Section: Discussionmentioning
confidence: 99%